Fungaemia in haematological malignancies: SEIFEM‐2015 survey. (7th March 2019) - Criscuolo, Marianna; Marchesi, Francesco; Candoni, Anna; Cattaneo, Chiara; Nosari, Annamaria; Veggia, Barbara; Verga, Luisa; Fracchiolla, Nicola; Vianelli, Nicola; Del Principe, Maria Ilaria; Picardi, Marco; Tumbarello, Mario; et al.
Abstract: Background: Fungal infections are still a relevant challenge for clinicians involved in the cure of patients with cancer. We retrospectively reviewed charts of hospitalized patients with haematological malignancies (HMs), in which a documented fungaemia was diagnosed between January 2011 and December 2015 at 28 adult and 6 paediatric Italian Hematology Departments. Methods: During the study period, we recorded 215 fungal bloodstream infections (BSI). Microbiological analyses documented that BSI was due to moulds in 17 patients (8%) and yeasts in 198 patients (92%), being Candida spp identified in 174 patients (81%). Results: Mortality rates were 70% and 39% for mould and yeast infections, respectively. Infection was the main cause of death in 53% of the mould and 18% of the yeast groups. At the multivariate analysis, ECOG ≥ 2 and septic shock were significantly associated with increased mortality, and removal of central venous catheter (CVC) survival was found to be protective. When considering patients with candidemia only, ECOG ≥ 2 and removal of CVC were statistically associated with overall mortality. Conclusions: Although candidemia represents a group of BSI with a good prognosis, its risk factors largely overlap with those identified for all fungaemias, even though the candidemia‐related mortality is lower when compared to other fungal BSI. Management of fungal BSI is still a complex issue, in which both patients and disease characteristics should be focused to address a personalized approach.